Analisis Penerimaan Aplikasi Kodifikasi Klinis Berbasis Web - Pramono, Angga Eko; Pratiwi, Rita Dian; Nuryati, Nuryati (Politeknik Negeri Jember, 2026)
The implementation of the clinical coding application has not yet been optimal, potentially due to limited application-based learning performance among students, system complexity, and insufficient lecturer support. This study employed the Unified Theory of Acceptance and Use of Technology (UTAUT) to further analyze user acceptance. Using a quantitative cross-sectional design, data were collected from 100 undergraduate students of Applied Health Information Management selected through simple random sampling. Data were obtained through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that Performance Expectancy, Effort Expectancy, and Social Influence have a positive and significant effect on Behavioral Intention (p-value < 0.05). Furthermore, Behavioral Intention significantly influences Use Behavior (p-value < 0.05), whereas Facilitating Conditions do not show a significant effect on Use Behavior (p-value > 0.05). These results indicate that the clinical coding application has met users’ expectations and supports their intention for continued use, despite suboptimal Facilitating Conditions. Therefore, enhancing bandwidth capacity is recommended to improve system accessibility and enable faster, simultaneous use by multiple users.